(untitled) (Castilla. Estudios de Literatura, 2020)
This article arranges a geopoetry of Amorfino. These selected couplets of love, which still beat in the Ecuador’s coastline, refer to geographical spaces to move feelings to the collective imaginary. The geopoetics category connects the spaces with symbols studied by the imagination psichology. The cognitive proposal uses intersemotic reading as an analytical frame inquire about the couplets and their poetic value. Generally, the references to river and hill reproduce, respectively, some senses of passing of time or irreversibility and of ascent or isolation. These representations show the mythical significance in some symbols acquire a more positive or negative character.